2016
DOI: 10.1002/pi.5101
|View full text |Cite
|
Sign up to set email alerts
|

Integrated three‐dimensional fiber/hydrogel biphasic scaffolds for periodontal bone tissue engineering

Abstract: Combining a tissue engineering scaffold made of a load-bearing polymer with a hydrogel represents a powerful approach to enhancing the functionalities of the resulting biphasic construct, such as its mechanical properties or ability to support cellular colonization. This research activity was aimed at the development of biphasic scaffolds through the combination of an additively manufactured poly( -caprolactone) (PCL) fiber construct and a chitosan/poly( -glutamic acid) polyelectrolyte complex hydrogel. By inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 66 publications
1
36
0
Order By: Relevance
“…The combination of a fibrous and a gelatinous phase can offer a plausible opportunity to optimize overall scaffold functionalities, such as mechanical properties, cellular migration, and biomimetic aspect (Puppi et al, ). Said composites mitigate pristine fiber and hydrogel drawbacks and amalgamate their benefits.…”
Section: Osteochondral Tissue Regenerationmentioning
confidence: 99%
“…The combination of a fibrous and a gelatinous phase can offer a plausible opportunity to optimize overall scaffold functionalities, such as mechanical properties, cellular migration, and biomimetic aspect (Puppi et al, ). Said composites mitigate pristine fiber and hydrogel drawbacks and amalgamate their benefits.…”
Section: Osteochondral Tissue Regenerationmentioning
confidence: 99%
“…As illustrated from the histological examination of the composite scaffold, morphologies of the osteoblasts could be observed around calcium phosphate inside the NFHGs, showing great prospect in practical application . Also, some other bone scaffolds of novel NFHGs were synthesized, such as biphasic scaffolds composed of porous PCL layers and chitosan (CS)/γ‐PGA polyelectrolyte complex hydrogels, hydrogel micropatterns composed of PCL/gelatin fibers and poly(ethylene glycol), self‐assembled peptide nanofiber hydrogels …”
Section: Applications Of Nfhgsmentioning
confidence: 99%
“…Therefore, it is eminently rational to propose that the mechanical behavior of the hydrogel materials could be effectively and dramatically improved by introducing fibers into the hydrogel matrix. Recently, different types of fiber‐enhanced hydrogels have been prepared via taking various fibrous materials as reinforcements, such as traditional fabrics, 3D‐printed microfiber frames, and novel nanofibers . Among those fibrous reinforcements, nanofibers can not only enhance the mechanical strength through increasing the stress dissipation along the interfaces between nanofibers and hydrogels, the network structure formed by the nanofibers can also greatly improve the performance and expand new application areas of hydrogel materials, which owe to the properties of large length–diameter ratio, high specific surface area, high porosity, unique chemical/physical and mechanical characteristic of nanofibers .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that this technique is well suited for the layered manufacturing of polymeric scaffolds with a predefined network of pores customized in terms of geometry and size, as well as with a given external shape that can resemble an anatomical part. The investigation of the CAWS fabrication process has led to the development of a set of layered scaffold prototypes made of biodegradable polyesters obtained from synthetic routes, such as PCL (Figs (c)–(f)), or from natural sources, such as poly[( R )‐3‐hydroxybutyrate‐ co ‐( R )‐3‐hydroxyhexanoate)] (PHBHHx) (Figs (g)–(i)).…”
Section: Computer‐aided Wet‐spinningmentioning
confidence: 99%
“…Polymeric scaffolds by CAWS. (a) Schematic of CAWS apparatus and (b) representative photograph of the layer‐by‐layer fabrication process . Representative (c) photograph and (d, e) SEM micrographs of PCL scaffolds, and (f) confocal laser scanning microscopy (CLSM) micrograph of MC3T3‐E1 preosteoblast cells cultured in vitro on PCL scaffolds (day 35) .…”
Section: Computer‐aided Wet‐spinningmentioning
confidence: 99%